Innovation in Road Construction Materials: A Study on the Combination of Biochar and Cement in Improving Subgrade Bearing Capacity - Respati, Rida; Salampak, Salampak; Sarie, Fatma; Jaya, Adi (JSE Journal of Science and Engineering, 2025)
Road infrastructure development often faces significant challenges due to low bearing capacity of the subgrade, especially when dealing with peat soil. This condition can lead to excessive settlement, deformation, and premature damage to the road pavement, resulting in high maintenance costs. Peat soil is inherently poor in quality, making it uneconomical to use as a subgrade for road pavements. The condition of peat soil significantly impacts road construction in Central Kalimantan Province. Therefore, one effective way to address this issue is through soil stabilization. This research aims to explore the potential of biochar and cement as stabilizing agents to improve the bearing capacity of peat soil. The study involves a series of laboratory tests, including initial physical property tests of the original peat soil, as well as index and mechanical strength tests after the addition of a combination of biochar and cement. The biochar used in this research is derived from coconut shells.The conducted tests include compaction tests to determine the maximum dry density and optimum moisture content, and CBR (California Bearing Ratio) tests to evaluate the soil's bearing capacity. The variations in biochar and cement addition were: 5% biochar with 5% cement, 5% biochar with 6% cement, 5% biochar with 7% cement, and 5% biochar with 8% cement. The research results indicate that the addition of biochar to peat soil stabilization mixtures using cement significantly increases the CBR value. Specifically, adding 8% cement and 5% biochar to peat soil was able to increase the CBR value by up to 9% from the original soil's CBR of 2.2%. Therefore, it can be concluded that the combination of biochar and cement can transform peat soil into a usable subgrade for road construction